An experimental and numerical study of the effect of diesel injection timing on natural gas/diesel dual-fuel combustion at low load. (1st September 2017) - Yousefi, Amin; Birouk, Madjid; Guo, Hongsheng
Abstract: Natural gas/diesel dual-fuel combustion compression ignition engine has the potential to reduce NOx and soot emissions. However, this combustion mode still suffers from low thermal efficiency and high level of unburned methane and CO emissions at low load conditions. The present paper reports the results of an experimental and numerical study on the effect of diesel injection timings (ranging from 10 to 50 °BTDC) on the combustion performance and emissions of a heavy duty natural gas/diesel dual-fuel engine at 25% engine load. Both experimental and numerical results revealed that advancing the injection timing up to 30 °BTDC increases the maximum in-cylinder pressure. However, with further advancing the injection timing up to 50 °BTDC, the maximum in-cylinder pressure decreases which is mainly due to the lower in-cylinder temperature before SOC. Moreover, the analysis of OH spatial distribution shows that, at very advanced diesel injection timings, the non-reactive zones are much narrower than later injection timings during the last stages of combustion, indicating a more predominant premixed combustion mode. At retarded diesel injection timings, the consumption of premixed fuel in the outer part of the charge is likely to be a significant challenge for dual-fuel combustion engine at low engine load conditions. However, with advancing the diesel injection timing, the OH radical becomes more uniform throughout the combustion chamber, which confirms that high temperature combustion reactions can occur in the central part of the charge. Diesel injection timing of 30 °BTDC appears to be the conversion point of all conventional dual-fuel combustion modes. Further advancing diesel injection timing beyond this point (30 °BTDC) results in noticeable reduction in NOx and unburned methane emissions, while CO emissions exhibit only slight drop. However, at very advanced diesel injection timings of 46 and 50 °BTDC, NOx and unburned methane emissions continue to drop, whereas CO emissions tend to increase. The results showed also that the highest indicated thermal efficiency is achieved at these very advanced diesel injection timings of 46 and 50 °BTDC. Finally, the results revealed that, by advancing diesel injection timing from 10 °BTDC to 50 °BTDC, NOx, unburned methane, and CO emissions are reduced, respectively, by 65.8%, 83%, and 60% while thermal efficiency is increased by 7.5%.